142 Evaluation of estrus detection patches as a tool to classify postpartum beef cows as estrous cycling or anestrous prior to the start of the breeding season. (30th November 2020) - Smith, Emily G; Bonacker, Rachael C; Andersen, Carson M; Thomas, Jordan M
Abstract: Estrus detection patches were evaluated as a tool to classify postpartum cows as estrous cycling or anestrous at the start of the breeding season. Estrotect TM Breeding Indicators were applied to 257 postpartum beef cows in three locations 25 days prior to the start of estrus synchronization. Coincident with the start of estrus synchronization, patches were scored using a 1 to 4 scale (1 = 0–25%; 2 = 25–50%; 3 = 50–75%; 4 = 75–100%) with scores of 3 or 4 considered activated. Blood samples were collected from each cow 10 days prior to, and at the start of the estrus synchronization. Serum progesterone concentrations were determined via radioimmunoassay; cows were considered estrous cycling if one or both samples exceeded a concentration of 0.5 ng/ml. Based on progesterone, 54.9% of cows were estrous cycling at the start of estrus synchronization. When missing patches were considered inconclusive results, use of patches to infer estrous cyclicity resulted in 85.0% sensitivity and 79.2% specificity with a positive predictive value of 87.2%. However, 75.1% of all cows presented with missing patches at the start of synchronization. If missing patches were considered activated, sensitivity was 95.7%, but specificity (16.4%) and PPV (58.2%) were poor, as 47.6% of cows presenting with missing patches were anestrous based on progesterone. Across all cows, pregnancy rate to AI was 58.0% (149/257). Cows with activated patches that were classified as false positives based on serum progesterone concentrations achieved a 71.4% (5/7) pregnancy rate to AI, raising questions as to whether sensitivity was underestimated due to inherent Type II errors in classification of cyclicity via progesterone. In summary, estrus detection aids are a sensitive tool to identify estrous cycling postpartum cows prior to the start of the breeding season; however, poor specificity and patch retention are limitations for this application.